Short-term mortality and implementation of antiretroviral treatment for critically ill HIV-infected children in a developing country. Issue 3 (2nd May 2006) - Cowburn, C; Hatherill, M; Eley, B; Nuttall, J; Hussey, G; Reynolds, L; Waggie, Z; Vivian, L; Argent, A
Abstract : Objective: To describe the short-term outcome of critically ill HIV-infected children with access to highly active antiretroviral therapy (HAART) in a developing region. Methods: Prospective observational study conducted in a paediatric teaching hospital in Cape Town, South Africa. All children admitted to the paediatric intensive care unit (PICU) with suspected HIV infection were screened. Data are n (%) with 95% confidence intervals. Results: Sixty eight of 96 HIV antibody-positive children, median age 3 months, were confirmed HIV-infected. Predicted PICU mortality was 0.42. Fifty one children (75%; 95% CI 65 to 85%) survived to PICU discharge, but hospital survival was only 51% (95% CI 40 to 63%). Limitation of intervention (LOI) decisions were a factor in the majority of PICU and ward deaths. Twenty one PICU survivors (31%; 95% CI 20 to 42%) commenced HAART, and two children were already on treatment. Nineteen children (28%) were considered to be established on HAART after 1 month. Thirteen HIV-infected children (19%; 95% CI 10 to 28%), representing 25% (95% CI 14 to 37%) of all PICU survivors, and 68% (95% CI 48 to 89%) of those PICU survivors who were established on HAART remain well on treatment after median 350 days. Conclusion: The majority of HIV-infected children survived to discharge from PICU, but only half survived to hospital discharge. LOI decisions, usually made in PICU, directly influenced short-term survival and the opportunity to commence HAART. Although few critically ill HIV-infected children survived to become established on HAART, the long-term outcome of children on HAART is encouraging and warrants further investigation.